“The Role of Financial Market in the Growth of Economy” - Jo’rayev Og’abek Oybek o’g’li (European Science Publishing, 2023)
The financial market is utmost fundamental for the growth of the economy. Financial markets are essential for the efficient resource allocation, liquidity provision, and risk reduction through diversification that occurs in capitalist economies1.A well-functioning financial market can improve capital allocation, mobilize savings, and promote investment. This article discusses the critical role played by the financial market in the growth of the economy.